Variable-speed air-to-air heat pump modelling approaches for building energy simulation and comparison with experimental data. Issue 2 (3rd March 2016) - Blervaque, Hubert; Stabat, Pascal; Filfli, Sila; Schumann, Mathieu; Marchio, Dominique
Abstract : The decrease in heat demand in low energy buildings and the development of new heating, ventilation and air conditioning systems call for a re-examination of the usual modelling approaches in building simulation. A comparison methodology is developed to confront different modelling approaches with experimental data. The methodology is applied to four models of variable speed air-to-air heat pumps. Two classical empirical models (a static and a dynamic one) and a detailed physical model are selected. Moreover, a simplified physical model is developed for this study. The detailed control of the experimental heat pump and a model of the defrost cycle are given. The four modelling approaches are compared to in situ measurements for outdoor temperatures between and including defrost phases. The simulation results are analysed from the point of view of building energy simulation.